Evaluation of the relationship of digital phototrichogram findings of patients with diffuse hair loss with blood TSH, ferritin and vitamin B12 levels - Bilik, Leyla; Kokcam, Ibrahim; Esen, Mustafa (Kare Publ, 2024)
OBJECTIVE: Telogen effluvium (TE) is a type of alopecia that is frequently seen in women. Among factors resulting in hair loss, many reasons such as endocrine diseases, nutrition disorders, stress, anemia, low ferritin levels, vitamin B12 deficiency, and thyroid diseases are found. A digital phototrichogram is one of the non-invasive methods of diagnosis in the evaluation of alopecia. In this study, it was aimed to compare biochemical parameters of female patients with diffuse hair loss with phototrichogram findings. METHODS: 108 female patients with diffuse hair loss were included in the study. Patients were divided into two groups: acute and chronic TE, and a hair pull test was applied. Total blood count, blood biochemistry, iron, iron binding capacity, ferritin, thyroid stimulating hormone (TSH), sT3, sT4, folic acid, and vitamin B12 levels were examined. The telogen/anagen ratios and hair densities of patients were determined with a phototrichogram RESULT: The serum biochemical parameters (aspartate aminotransferase, alanine aminotransferase, urea, creatinine), TSH, sT3, sT4, and folic acid levels of patients were within normal limits. Telogen ratio, anagen ratio, hair density, number of shed hairs, family history, blood ferritin, TSH, and vitamin B12 levels were found to be similar between groups having acute and chronic TE. In our study, while mean anagen and telogen ratios with trichoscan were similar to literature data, no statistically significant correlation was determined between patients' ages and examined trichoscan findings (p>0.05). The hair pull test positivity of patients with chronic TE was higher compared to patients with acute TE (p<0.05). In patients with positive hair pull tests, the telogen ratio and hair density were found to be higher. In the group with <40 ng/mL ferritin level, the mean telogen ratio was detected to be significantly higher than the mean anagen ratio (p<0.05). No significant correlation was determined between vitamin B12 and TSH levels in patients and phototrichogram findings (p>0.05). CONCLUSION: The findings of this study showed that ferritin has an important role in diffuse hair loss, and the phototrichogram method is an auxiliary method for the physician in the diagnosis of TE.
Keywords: Digital phototrichogram; ferritin; telogen effluvium